RANCANG BANGUN PERANGKAT LUNAK DAILY ACTIVITY DOSEN (Studi Kasus : FKOM-UNIKU) - Fahmi Yusuf; Erlan Darmawan; Yeye Fajriani (NUANSA INFORMATIKA, 2010)
ABSTRACTDaily activities performed by the lecturers at a university to be a complicated process lecturers are doing business outside of the university. This is because the lecturer will find Â difficulties to collect data about the activities commonly performed in the university, it will be difficult for employers in searching information about the presence of teachers, and it will be difficult also for lecturers in getting information about teaching schedule. That can only be seen at the university. Likewise, students should go to the university to find information about the presence of lecturers through their teaching schedule.Therefore by making a system of daily activity can help lecturers to continue performing their activities outside the university and conduct activity data can be sent via mobile phone to the server by using the SMS Gateway. Lecturers activity data can also be accessed by students as information.The Server-based SMS Center is made online managed by the admin and lecturers can access it with different access right. it is done so that each lecturer can input data such as schedules, other activities as well as an online agenda that will also be accessible through the system Daily Activity-base SMS Gateway.The results of this system in the form of the output from the server to the user who sends the input data in a certain SMS format. This software is made with J2ME programming language and SMS-based Center online using PHP MySQL.Keyword : Daily, activities, lecturers, sms, J2ME